A review of organizational relationship quality, trust, commitment and lecturers’ perceived performance in institution of higher learning / Zainuddin Zakaria ... [et al.] - Zakaria, Zainuddin; Nik Hassan, Nik Fakrulhazri; Abdullah, Nurmuslimah Kamilah; Ngah, Nazlin Emieza; Ismail, Rusnah; Siahaan, Elisabet (Universiti Teknologi MARA, Perlis, 2021)
As a result of globalization and the influence of working remotely, it has become more important to develop high-quality relationships in the organization for more cohesive teamwork among employees. High cohesiveness and synergy among employees will help organizations to achieve their goals. Management needs to understand how to interact with employees in ways that boost job satisfaction and engagement as perceived by employees. Many scholars agree that organizational performance is an indicator of how well an organization attains its desired goals. In addition to the roles played by the managers and superiors, organisational performance is also dependent upon the synergy of each employee’s performance and their teamwork. Whether it is private or government agencies, service or manufacturing, employee performance is very important. In this paper, we hope to discuss and describe the relationship between three elements of Organizational Relationship Quality with the lecturer performance. The dimensions of Organizational Relationship Quality include Organizational Trust, Organizational Commitment and Organizational Relational Norms. In addition, we hope to better understand the relationship and how the dimensions of relational norms are associated with a lecturer’s performance in an institution of higher learning.